A Simplistic Approach in Estimating Paleo- Bathymetry by Using Seismic Stratigraphic Features in Fluvial-Dominated Delta - Agus Susianto (Berita Sedimentologi, 2011)
The advance of high resolution 3D seismic technology has enabled much detailed imaging not only for structural features, but also for detailed stratigraphic features. If we squeeze a little bit more out of seismic data, it can provide us some important information. Seismic stratigraphy analysis in a prograding delta setting can deliver simple yet useful tool in understanding the geological and depositional aspects from seismic data. Recognizing unique seismic stratigraphic pattern of each part of delta and their chronostratigraphic correlative unit will allow us to understand the depositional relief of ancient delta sequence observable in seismic. This article discusses how to do simple estimation of paleobathymetry in a fluvial dominated delta and its limitation. This is a little effort to make seismic interpretation more meaningful and much more fun.